The Bodleian Daybook and the purchase of second-hand books - Atkin, T (Oxford University Press, 2024)
Oxford, Bodleian Library, MS Library Records e.9 (the Daybook) is a ‘Book of Accompts for the Librarie’ that covers the seven-year period following the death of Sir Thomas Bodley. In it are details of two consignments of second-hand books purchased by the Bodleian from the London bookseller John Edwards in 1613 and 1615. Taking these lists as a starting point, this article considers the relationship between the Bodleian and Edwards; the subject and condition of the items purchased; as well as their value and price. Underpinning the discussion is a survey of 226 of the second-hand items bought from Edwards that remain extant within the Bodleian. Together, the evidence provides unrivalled detail about the trade practices involved in the sale of second-hand books to one of England’s first ‘publick’ libraries.